Оцінка фізичної активності студентів НТУ "ХПІ" за допомогою міжнародного опитувача IPAQ - Натарова, Вікторія Вікторівна; Натаров, Володимир Олександрович; Недбайло, Ірина Анатоліївна (Національний педагогічний університет ім. М. П. Драгоманова, 2019)
У дослідженні брали 116 студентів 1-3 курсів НТУ "ХПІ" основної медичної групи. Результати обробки анкет з фізичної активності (ФА) з використанням стандартного протоколу опитувача International Physical Activity Questionnaire показали, що 80% студентів мали високий рівень ФА, 18% – середній, і тільки 2% студентів мали низький рівень ФА. При альтернативній обробці даних опитувача IPAQ з використанням мінімальних норм ФА, рекомендованих ВООЗ виявили 13,9% студентів, які мають рівень ФА нижче рекомендованих мінімальних норм. Середній рівень фізичної активності студентів у тиждень склав 9014±872 МЕТ×хв×тиждень-1. Опитувач IPAQ показав, що тільки 2% з опитаних студентів основної медичної групи малі критично низький рівень ФА. Ці дані узгоджуються з результатами закордонних авторів, що використовували цю же методику.

Estimation of physical activity (PA) 116 students of 1-3 courses of NTU "KhPI" conducted by the method of questionnaire with the use of IPAQ. The results were processed using methods of mathematical statistics (average value, error of the average value of the studied sample sets, Student’s T-test to verify the equality of the average values in two samples). As a result of treatment of questionnaires on PA with the use of standard protocol of IPAQ students were divided into 3 groups. 80% students were had high level of FA, 18% - middle, and only 2% students were had low level of PA. At the alternative processing of data of questionnaire of IPAQ with the use of the minimum norms of PA, recommended WHO got 13,9% students, having a level of PA of the below recommended minimum norms. The middle level of physical activity of students in a week made 9014±872 МЕТ×min×week-1. At the estimation of the time conducted in sitting position in workday and weekend 6,4±0,5 and 5,6±0,3 hour accordingly, distinctions are not reliable (р>0,05). The sufficient level of physical activity is fundamental for successful adaptation to educational activity. The questionnaire of IPAQ showed, what only 2% from the polled students of basic medical group had a low level of PA critically. These data comport with data from foreign sources using the same methodology. Prospectively continue the analysis of FA students throughout their study of higher education institutions and identify the level of FA of students of a special medical group.
Estimation of physical activity of students of NTU "KhPI" by means questionnaire IPAQ
Keywords: навчальний процес; студенти; анкетування; фізична культура; соматичне здоров'я; students; physical activity; questionnaire; somatic health